Safety of liposome extended-release bupivacaine for postoperative pain control - Portillo, Juan; Kamar, Nawal; Melibary, Somayah; Quevedo, Eduardo; Bergese, Sergio (Frontiers in Pharmacology, 2014)
Background: Ideal postoperative pain management requires a multidisciplinary approach in combination with a variety of dosage regimens. Approximately 21-30% of patients experience moderate to severe pain in the postoperative period, which may have a significant impact on recovery rate, standard of living, psychological health, and postoperative complications. Objective: Analysis of the incidence and characterization of reported adverse effects with DepoFoam bupivacaine compared to conventional bupivacaine or placebo. Methods: A systematic review of prospective studies on the use of DepoFoam versus bupivacaine or placebo was performed in order to answer the clinically-relevant question: Is DepoFoam a safer formulation in place of bupivacaine single injection or continuous local infusion techniques for postoperative pain management? Inclusion criteria required randomized, controlled, double-blind trials in patients 18 years old or older, single dose used for postoperative pain control, and a primary procedure performed. Results: Six studies fit the inclusion criteria for analysis, DepoFoam bupivacaine used in therapeutic doses was well-tolerated, had a higher safety margin, and showed a favorable safety profile compared to bupivacaine and control groups. Conclusion: Extended drug delivery system of DepoFoam bupivacaine is a promising drug formulation that may significantly improve postoperative care and pain control in surgical patients.